Dissolved Organic Carbon Flux On Forest Toposequences in Jambi, Indonesia - Murtilaksono, Kukuh; Anwar, Syaiful; Hartono, Arief; Sunarti, Sunarti; Kuzyakov, Yakov; Putra, Gilang Sukma; Arifin, Syamsul; Sustama, Achmad Surya Adi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2019)
DOC fluxes were studied within soil profiles on forest toposequences transect of Bukit Dua Belas National Park and Harapan Forest, Jambi, Indonesia. DOC concentration was determined using NPOC (Non Purgeable Organic Carbon) method. Amount and DOC flux from soil horizons on the lower slope was significantly higher than that from the middle and the upper slopes. Amount and DOC flux from AO soil horizon was significantly higher than that from AB and B soil horizons. DOC was maximally accumulated from AO soil horizon of soil profile on lower slope during rainy season.